(untitled) (European Journal of Pure and Applied Mathematics, 2026)
Preventing airborne disease transmission in built environments is critically important for public health. This study employs computational fluid dynamics to evaluate the performance of ceiling-mounted air curtains in controlling the spread of airborne bacteria within an office space. Multiple simulations were conducted, varying the air curtain’s supply velocity, while predicting the concentration of bacteria in the inhaled air of an exposed occupant to assess the system’s effectiveness. The results showed that, in a 2.8-m-high office, an air curtain ejection velocity of 1.5 m/s yielded optimal performance, improving the inhaled air quality by up to 96%. At lower velocities, the air curtain failed to effectively counteract pathogen diffusion, resulting in reduced protection. Conversely, excessively high velocities disrupted airflow patterns and compromised the separation between localized zones, thereby diminishing the curtain’s effectiveness.